2013
DOI: 10.1039/c2gc36776a
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward heterogeneous palladium catalyzed synthesis of aryl ethers and aryl amines via a solvent free aerobic and non-aerobic dehydrogenative arylation

Abstract: Aryl ethers have been prepared from cyclohexanone derivatives and various alcohols in the presence of a catalytic amount of palladium on charcoal. The formation of an enol ether followed by an aerobic or non-aerobic dehydrogenation reaction, seem to be the key steps of this transformation. In addition, this new method was also adapted for the synthesis of arylamines.Scheme 1 Envisaged methodology for the synthesis of aryl ethers by a heterogeneous catalyzed solvent free dehydrogenative arylation using cyclohex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 62 publications
1
45
1
Order By: Relevance
“…22,23 And, Imahori et al recently reported a Pd-catalyzed C–H arylation-aromatization of cyclohexenone that furnishes 4-arylphenol derivatives, again consistent with Pd-mediated cleavage of the allylic C–H bond. 12b …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 And, Imahori et al recently reported a Pd-catalyzed C–H arylation-aromatization of cyclohexenone that furnishes 4-arylphenol derivatives, again consistent with Pd-mediated cleavage of the allylic C–H bond. 12b …”
Section: Resultsmentioning
confidence: 99%
“…A number of related transformations, including reactions for the synthesis of aryl ethers and anilines from cyclohexanones and cyclohexenones, have been reported by other groups over the past year. 12 …”
Section: Introductionmentioning
confidence: 99%
“…16 Both cyclohexanones and cyclohexenones were effective substrates, as well as tetralones (Scheme 10). …”
Section: Dehydrogenation Of Cyclohexanones and Cyclohexenones To Pmentioning
confidence: 99%
“…2 In many cases, these methods enable synthesis of aromatic compounds with substitution patterns and/or functional groups that are difficult to access via traditional aromatic functionalization reactions. This strategy has been employed by us and others in Pd-catalyzed methods for the conversion of cyclohexanone and cyclohexenone derivatives into substituted phenols, 3 aryl ethers 4 or anilines 5 and for the conversion of cyclohexene derivatives into substituted arenes. 6 More recently, we began exploring methods for aerobic dehydrogenation of partially saturated N -heterocycles to heteroarenes.…”
mentioning
confidence: 99%